ON USING VIDEO CONFERENCE SYSTEMS IN HIGHER SCHOOL FOR DISTANCE LEARNING - D V Senashenko; M A Senashenko (RUDN Journal of Informatization in Education, 2015)
The article describes distant learning systems used in world practice. The author gives classification of video communication systems. Aspects of using Skype software in Russian Federation are discussed. In conclusion the author provides the review of modern production video conference systems used as tools for distant learning.